Frozen Storage Studies of Mince Based Products Developed from Tilapia (Oreochromis mossatnbicus, Peters 1852) - Ninan, George; J., Bindu; Joseph, Jose (Fishery Technology, 2025)
Tilapia (Oreochromis mossambicus) is a relatively abundant, low value fish that has wide distribution in India due to its adaptability to different environments. In India, the fish has limited scope for consumption in the fresh form. This study is an attempt to explore the possibilities of better utilization of this species by development of mince-based value added products and the evaluation of shelf life during frozen storage. Mince from Tilapia was used for the preparation of value added products viz., chilly fish, fish cutlet and fish balls. The biochemical and sensory parameters were analysed to study the quality changes and shelf life of these products in frozen storage at - 20 0 C. The products had a good shelf life of 18 to 21 weeks in frozen storage.